Serum neurofilament levels correlate with retinal nerve fiber layer thinning in multiple sclerosis. (November 2020) - Bsteh, Gabriel; Berek, Klaus; Hegen, Harald; Teuchner, Barbara; Buchmann, Arabella; Voortman, Margarete M; Auer, Michael; Wurth, Sebastian; Zinganell, Anne; Di Pauli, Franziska; Deisenhammer, Florian; Khalil, Michael; et al.
Background: Serum neurofilament light chain (sNfL) levels and peripapillary retinal nerve fiber layer (pRNFL) are both emerging biomarkers of neuro-axonal damage in multiple sclerosis (MS). However, data on the relation between sNfL and pRNFL are scarce. Objective: We aimed to determine the relation of sNfL levels with pRNFL thinning in a large cohort of relapsing–remitting (RR) MS patients. Methods: We identified 80 patients from a prospective, 3-year observational study on retinal changes in RRMS with annual blood samples available. sNfL levels were measured using single-molecule array (Simoa TM ) assay. Annualized loss of pRNFL (aLpRNFL) was determined by individual linear regression models. Correlations between single and repeated sNfL levels and aLpRNFL were analyzed using multivariate linear regression and mixed-effect models. Results: After correction for sex, age, and baseline sNfL, an sNfL increase of 10 pg/mL was associated with an aLpRNFL of −0.7 µm (95% confidence interval (CI): (−1.3, −0.2), p  < 0.001). Patients with ⩾2 sNfL measurements >75th percentile displayed higher aLpRNFL (2.2 µm, standard deviation (SD) 0.6) compared to patients with no sNfL measure >75th percentile (0.4 µm, SD 0.2, p  < 0.001). Between 15% and 20% of the aLpRNFL variance could be predicted from sNfL levels. Conclusion: sNfL levels contribute to the prediction of retinal thinning in patients with RRMS, strengthening its value as a biomarker of neuro-axonal damage.